Treat and Restore Compromised Sockets Immediately with the Novel Vestibular Socket Therapy : A Revolution in Immediate Implant Placement (Global Journal of Medical Research, 2022)
Immediate implant placement is now-a-days one of the promising modalities for replacing missing teeth as it helps restore form and function for a patient within a short period of time. However, presence of active infection within such freshly extracted sockets could jeopardize the success of aforesaid therapy. Although, a variety of techniques have been studied till date, there still remains a need for a treatment modality that could restore freshly extracted infected sockets with inadequate hard tissues. Since presence of adequate hard and soft tissues surrounding an implant is essential for prognosis of dental implant. A novel treatment modality named as Vestibular Socket Therapy (VST) has gained popularity to conventional two-staged approach for restoring infected sockets.
Keywords: immediate implants; infected sockets; bone grafts; sub-epithelial connective tissue grafts